Antinociceptive activity of petroleum ether fraction obtained from methanolic extract of Clinacanthus nutans leaves involves the activation of opioid receptors and NO-mediated/cGMP-independent pathway - Zainul Amiruddin Zakaria; Mohammad Hafiz Abdul Rahim; Mohd Hijaz Mohd Sani; Maizatul Hasyima Omar; Siew Mooi Ching; Arifah Abdul Kadir; Qamar Uddin Ahmed (BMC, 2019)
Abstract Background Methanol extract (MECN) of Clinacanthus nutans Lindau leaves (family Acanthaceae) demonstrated peripherally and centrally mediated antinociceptive activity via the modulation of opioid/NO-mediated, but cGMP-independent pathway. In the present study, MECN was sequentially partitioned to obtain petroleum ether extract of C. nutans (PECN), which was subjected to antinociceptive study with aims of establishing its antinociceptive potential and determining the role of opioid receptors and l-arginine/nitric oxide/cyclic-guanosine monophosphate (l-arg/NO/cGMP) pathway in the observed antinociceptive activity. Methods The antinociceptive potential of orally administered PECN (100, 250, 500 mg/kg) was studied using the abdominal constriction-, hot plate- and formalin-induced paw licking-test in mice (n = 6). The effect of PECN on locomotor activity was also evaluated using the rota rod assay. The role of opioid receptors was determined by pre-challenging 500 mg/kg PECN (p.o.) with antagonist of opioid receptor subtypes, namely β-funaltrexamine (β-FNA; 10 mg/kg; a μ-opioid antagonist), naltrindole (NALT; 1 mg/kg; a δ-opioid antagonist) or nor-binaltorphimine (nor-BNI; 1 mg/kg; a κ-opioid antagonist) followed by subjection to the abdominal constriction test. In addition, the role of l-arg/NO/cGMP pathway was determined by prechallenging 500 mg/kg PECN (p.o.) with l-arg (20 mg/kg; a NO precursor), 1H-[1, 2, 4] oxadiazolo [4,3-a]quinoxalin-1-one (ODQ; 2 mg/kg; a specific soluble guanylyl cyclase inhibitor), or the combinations thereof (l-arg + ODQ) for 5 mins before subjection to the abdominal constriction test. PECN was also subjected to phytoconstituents analyses. Results PECN significantly (p < 0.05) inhibited nociceptive effect in all models in a dose-dependent manner. The highest dose of PECN (500 mg/kg) also did not significantly (p > 0.05) affect the locomotor activity of treated mice. The antinociceptive activity of PECN was significantly (p < 0.05) inhibited by all antagonists of μ-, δ-, and κ-opioid receptors. In addition, the antinociceptive activity of PECN was significantly (p < 0.05) reversed by l-arg, but insignificantly (p > 0.05) affected by ODQ. HPLC analysis revealed the presence of at least cinnamic acid in PECN. Conclusion PECN exerted antinocicpetive activity at peripheral and central levels possibly via the activation of non-selective opioid receptors and modulation of the NO-mediated/cGMP-independent pathway partly via the synergistic action of phenolic compounds.